The Effect Of Single Leg Depth Jump Pliometric Training On Leg Muscle Power In Athletes Of SD Negeri 01 Central Bengkulu - Saputra, Caca; Sumantri, Ajis; Perdima, Feby Elra (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
Sport is a physical activity that has a specific purpose and is carried out with certain rules systematically such as the existence of time rules, pulse targets, the number of repetitions of movements and others carried out with recreational elements. The design used in this study is a one-group pretest-posttest design, a one-group pretest-posttest design is a type of research in which there is a pretest before treatment and there is a posttest after treatment. This design requires a group that is selected according to research needs. This design provides tests three times on Dehasen University volleyball athletes Bengkulu. Based on data analysis and discussion that has been presented earlier, several conclusions can be stated as follows: Single leg defth jump pliometric exercise has a significant effect on leg muscle power of SD Negeri 01 Bengkulu Tengah athletes, where the results obtained tcount> ttable = 6.752> 2.060.